WIDE ANGLE SCATTERING IN QUANTUM ELECTRODYNAMICS - Cardy, J (1971)
We study high energy elastic electron-electron scattering at wide angles in quantum electrodynamics. The amplitude is predicted to decrease exponentially with increasing energy, in agreement with strong interaction data. © 1969.